Forty Years of Reform and Poverty Reduction : Remarks at the International Forum on China’s Reform and Opening Up and Poverty Reduction - Kim, Jim Yong (World Bank, Washington, DC, 2019)
Jim Yong Kim, President of the World Bank Group, spoke about the following: i) understand China’s journey and get the historical record right; ii) understand China’s past reforms, because they are important for future reforms; iii) understanding China’s reforms is increasingly important for the rest of the world; iv) china’s reform and opening up program, which was the foundation for the rapid growth that allowed people to lift themselves out of poverty; v) a focused and sustained effort targeted at poverty reduction throughout the reform period.